A Case of Malaria Predisposing to Salmonella Bacteremia in a Returning Traveler from Nigeria. (27th September 2018) - Jakubowski, Robert; Steed, Lisa L.; Dorman, Susan E.; Marculescu, Camelia
Abstract : We describe a febrile adult returning to the U.S. from Nigeria. Malaria was diagnosed by rapid antigen testing, but recognition of invasive nontyphoidal Salmonella disease was delayed. While the moniker, "typhomalaria, " once used to describe an illness with features of malaria and typhoid fever, has fallen out of favor, it may nevertheless be a helpful reminder to clinicians that both infectious diseases can arise in the same patient. Blood cultures should be obtained routinely in febrile returning travelers from malaria-endemic regions, including those in whom the diagnosis of malaria has already been established.